2006
DOI: 10.1111/j.1467-8683.2006.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Boards of Directors of Publicly‐Held Companies in Brazil: profile and implications for minority shareholders

Abstract: We analyse the profile of the boards of directors of 142 Brazilian publicly-held companies in 1999. Directors were divided into four distinct categories, following Bhagat and Black (2000 Working Paper no. 143, Columbia Law School) criteria for the US market. Our survey analyses the degree of independence of directors in relation to their respective controlling shareholders. Our results indicate that the controlling shareholders' representatives largely dominate the boards. One intriguing finding is that minori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…When the controlling family is conservative in investment strategies or intends to entrench self‐interests, they will select board members or CEOs who will follow the family's direction. As a result, the selected directors or CEOs may choose venturing projects with low risk or high benefit to family shareholders (Saito & Dutra, 2006; Yeh & Woidtke, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…When the controlling family is conservative in investment strategies or intends to entrench self‐interests, they will select board members or CEOs who will follow the family's direction. As a result, the selected directors or CEOs may choose venturing projects with low risk or high benefit to family shareholders (Saito & Dutra, 2006; Yeh & Woidtke, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Because ownership is often largely concentrated, the potential conflicts between majority and minority shareholders are generally more pronounced (e.g., Claessens and Fan, 2002;Claessens and Yurtoglu, 2013;Djankov et al, 2008). For this reason, Saito and Dutra (2006) argue that minority shareholders and the firm itself suffer from a dependency problem between the controlling shareholder and the board of directors. Hence, the structure and composition of board structure in such countries is crucial and there is a need for an appropriate mix (i.e., diversity) of board members combined with other governance mechanisms (e.g., independent directors, presence of block holders, et cetera).…”
Section: Related Literature and Research Focusmentioning
confidence: 99%
“…Further, voting shareholders who own 10 percent of the voting share capital, and the group of non‐voting shareholders, may elect one Fiscal Council member each. Previous studies indicate that minority rights have been increasingly employed by smaller shareholders: in 1999, Saito and Dutra () found that the majority of Brazilian minority investors were not using the mechanisms provided by the legislation to elect directors onto boards of directors, while, in 2005, Black et al () found that 41 percent of the 116 Brazilian firms they surveyed had one or more representatives of the minority shareholders.…”
Section: Research Context: Brazil and South Africamentioning
confidence: 99%